ANALISIS KETERAMPILAN PENGOPERASIAN PROGRAM MYOB PADA SISWA KELAS XI AK DI SMKN 3 PONTIANAK - Herdiyanti, Lina; Genjik, Bambang; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract Computer accounting is one of the productive subjects in vocational schools. One application that is used is MYOB (Mind Your Own Business). The general problem that was tried to be raised in this study was "Analysis of the Operational Skills of the MYOB Program in class XI AK students at SMK Negeri 3 Pontianak". The method used in this research is descriptive method with a form of qualitative research. Based on the results of the study through the answers to the interview and also based on the observation that the analysis of the MYOB program operating skills in class XI AK SMK Negeri 3 students was very good. Students are able to fill in the command columns smoothly and are able to continue practice step by step Keywords:   Analysis, Skills, MYOB Program